Seroprevalence of Toxoplasma gondii in Dairy Cattle with Reproductive Problems in Sudan. (18th September 2013) - Elfahal, Abdelghafar M.; Elhassan, Amira M.; Hussien, Mohammed O.; Enan, Khalid A.; Musa, Azza B.; El Hussein, Abdelrahim M.
Abstract : Toxoplasmosis, caused by Toxoplasma gondii, is one of the most common parasitic infections of humans and other warm-blooded animals in most parts of the world. The disease is common among sheep and goats and it is recognized as one of the major causes of reproductive failure in these animals. Cattle, on the other hand, can be infected, but abortion or perinatal mortality has not been recorded. This survey was carried out to study the prevalence of this disease in cattle in Khartoum and Gazira States (Sudan). 181 sera samples collected from dairy cattle with reproductive problems were assayed for antibodies to T. gondii by ELISA. The prevalence rate of T. gondii antibodies in cattle at herd level was 44.8% (13/29). Herd level infection rates were 50% and 33.3% in Khartoum and Gazira States, respectively. The overall prevalence of T. gondii at individual level in both states was 13.3% (24/181). The prevalence was 12.7% (17/134), was 14.9% (7/47) in Khartoum and Gazira State, respectively. There was significantly higher (P < 0.05 ) prevalence of T. gondii antibodies in the age group less than one year old (36.4%) than in other age groups and in males (30.8%) than in females (11.9%) while no significant relationship was discerned regarding breed, location, season, or signs of reproductive disease.